Penerjemahan Komunikatif Lagu Shabry yang Dipopulerkan oleh Sherine Abdel Wahab - Nurfathin Nuha, Siti Zulfa; Fatawi, M Faisol; Ahmad, Mehdi; Surur, Misbahus (Jurnal Al-Maqoyis, 2024)
In the digital age, music knows no geographical boundaries. Songs from various countries, including Arabic, can easily reach listeners around the world. An example is the songs of Sherine Abdel Wahab, a famous Egyptian singer whose works have gone viral on social media platforms, especially among TikTok users in Indonesia. This is because the millennial generation is now inclined to things that are going viral on social media, especially TikTok. For speakers of languages other than Arabic, especially Indonesian speakers, hearing Arabic songs is still an obstacle, especially enjoying the full meaning of these songs. Therefore, communicative translation of Arabic song lyrics is important to bridge the language and cultural differences. This study aims to find out the application of communicative methods and strategies used in translating the song "Shabry Aleel" popularized by Sherine Abdel Wahab. The method used in this research is qualitative with a descriptive approach, focusing on the research of translating the song Shabry Aleel popularized by Sherine Abdel Wahab as the object of research. After translating the object of the data, academic accountability of the results of the translation is carried out by describing the methods and strategies used. The communicative method research on the translation of Shabry Aleel's song popularized by Sherine Abdel Wahab is very suitable, because in addition to paying attention to communicative principles, the resulting translation is also very easy to understand by the target readers. In addition to using the communicative method, the strategies used in this research include (taqdim and ta'khir) on the subject and predicate patterns of the target language, removing (hadzf) and replacing (tabdil) on the meaning of the translated words so that the results are easier to understand.